(untitled) (European Journal of Marketing and Economics, 2020)
This paper approaches the evolution of the final consumption recorded at the level of Albanian economy. According to statistical methodology the public and private consumption are two of the components of the final consumption. The main variable of our study is final consumption, which is set to be influenced by at least two independent variables, such as public and private consumption. Lately, Albanian economy has been presented with a new and different macro economic policy, a new form of partnership of investments between public and private sector. We are highly interested in the impact of these changes on final consumption .The correlation between the main parameter and its influence factors is analyzed through a regression model. Eviews is the software that the data will be processed under standard methods. The model and the results are part of the paper. To be emphasized is that the reliability of the multiple regression model does not exclude the possibility to analyze the single correlation between the parameters, in parallel.